Effect of Cascade Surface Roughness on Boundary Layer Flow Under Variable Conditions - Liu, C.; Li, Y.; Zhou, Z.; Wiśniewski, P. (Frontiers in Energy Research, 2022)
Under the influence of many factors, the surface roughness of the cascade will change during turbomachinery operation, which will affect the boundary layer flow of the cascade. In this paper, the effects of cascade surface roughness on boundary layer flow under variable conditions are analyzed by experiment and numerical simulation. The results show that, with the increase of roughness, the total pressure loss coefficient of cascade decreases first and then increases. The larger the Reynolds number is, the greater the total pressure loss coefficient is, and the sensitive area of loss change is changed. In the sensitive area, the roughness has a greater influence on cascade loss. There are separation bubbles at the suction front edge of smooth cascades. With the increase of roughness, the degree of turbulence increases, the transition process is accelerated. When the roughness is between 74 μm, and 150 μm, the separation bubble disappears and the separation loss decreases. In conclusion, the aerodynamic loss of cascade increases with the increase of roughness, and the cascade efficiency decreases. However, roughness can restrain the flow separation and reduce the separation loss. The two have gone through a process of one and the other. At 0.45 C_x and later positions, the boundary layer thickness shows a trend of decreasing first and then increasing, but the overall boundary layer thickness has little change. When the roughness is 74 μm, the displacement thickness, momentum thickness and shape factor at the back of the cascade are the minimum.